Linear Superposition of Retinal Action Potentials to Predict Electrical Flicker Responses from the Eye of the Wolf Spider, Lycosa baltimoriana (Keyserling) - DeVoe, Robert D. (The Rockefeller University Press, 1962)
Retinal action potentials were elicited from light-adapted posterior median ocelli of the wolf spider Lycosa baltimoriana (Keyserling) by rectangular shaped photic stimuli representing 8 per cent increments or decrements of the background illumination. Responses to trains of recurrent incremental or decremental flashes were successfully predicted by graphical linear superposition of a single flash response, which was repeatedly drawn and added to itself at intervals equal to the period of the intermittent stimulus. Incremental stimuli inverted to form decremental stimuli elicited responses which were also inverted. Responses to single incremental flashes were successfully predicted by linear superposition of the response to one incremental step stimulus, which was inverted and added to itself at an interval equal to the duration of the flash.